DEVELOPMENT OF CRITICAL LITERACY BASED-CRITICAL READING MODEL AS A LEARNING MODEL - Yusniati Rambe (Journal of Indonesian Language Education and Literary, 2017)
The aim of this study is to develop a model of critical reading based on critical literacy as an instructional model in teaching Reading at SMAN (Senior High School) 1 District Bombana, in Southeast Sulawesi. It needs to do a needs analysis, assessment of teaching materials are being used and are already in use, the development of models of teaching materials, test the feasibility of the model, and test the effectiveness of the design of the model. This study is a developmental research. The study design was qualitative and quantitative. An experiment in this study was small and large groups. Results of the study revealed the following. First, the teaching materials that were already being used in the subjects of Reading had not met the expectations of English teachers so that required an approach, skills, and reading different types of activities. Second, teaching materials that were already being used in Subjects Reading characterized only do the questions on the grounds of practicality. Third, the product model of teaching materials developed based on the principles of pedagogic critical literacy. Fourth, based on expert review on the models of these materials to be feasible with some small notes. Fifth, readability test results showed that the model of teaching materials had a reading level appropriate to the level of English proficiency level of students. Sixth, the results of testing the effectiveness of product models showed that a model of teaching materials teaching materials critical reading proven effective in improving students' critical reading skills.